Synthesis and luminescence behavior of Ba2SiO4:Dy3+ phosphors in presence of charge compensator ions. Issue 1 (March 2020) - Banjare, Ganesh Ram; Bisen, D.P.; Brahme, N.; Belodhiya, Chitrkant; Upadhyay, A.K.
Abstract: A series of dysprosium (Dy 3+ ) doped barium ortho-silicate (Ba2 SiO4 ) phosphors were synthesized by conventional Solid State reaction technique. In order to find out the phase purity and crystal structure, characterization of the prepared powder samples was done by X-ray diffraction (XRD) method. FTIR method confirms the presence of all elemental compositions. Photoluminescence (PL) properties were studied. The PL spectra was observed to study the effect of concentration of Dy 3+ ion and it is found that the prepared phosphors show two strong emission peaks in the blue and yellow region at 478 nm and 573 nm, respectively, when excited by the near-ultraviolet (UV) of wavelength 348 nm. The critical distance between the Dy 3+ ions was calculated using Blasse's equation. Effect of monovalent ion K + was examined as a charge compensator ion and observed that co-doping of charge compensator ion enhances the luminescence intensity. Chromaticity coordinates of the phosphor are found near to white light region, which confirms their applicability in solid state lighting applications; especially in white-LEDs.